2019
DOI: 10.1002/pssr.201900474
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of an InAs(Sb)/InxGa1−xAsySb1−y Type‐II Superlattice

Abstract: Infrared optoelectronic devices based on type‐II superlattice structures of III–V semiconductor materials have progressed significantly during the past decades. Exploring and further expanding the material space is of great significance for the development of infrared applications. Herein, a superlattice structure based on InAs(Sb)/InxGa1−xAsySb1−y grown using a fractional monolayer alloy process to control the superlattice composition and structure is presented. High‐order satellite peaks with a narrow full w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…bromine [159] and 1-(4-ethenylbenzyl)-3- (3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctylimidazolium iodide (ETI) [160] were used as additives in MA + -contained perovskite precursor solutions. In the latter case, it was shown that the formation of hydrogen bonds between ILs and MA restrains the MA + cation movement from bulk to the surface, resulting in enhanced thermal stability (Figure 11d).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…bromine [159] and 1-(4-ethenylbenzyl)-3- (3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctylimidazolium iodide (ETI) [160] were used as additives in MA + -contained perovskite precursor solutions. In the latter case, it was shown that the formation of hydrogen bonds between ILs and MA restrains the MA + cation movement from bulk to the surface, resulting in enhanced thermal stability (Figure 11d).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The improvement of performance as well as stability was attributed to beneficial effects observed with the use of IL BMIMBF4 such as enlarged grains, improved energetic alignment at interfaces, improved interaction between perovskite and NiO HTL, and suppressed ion migration. In other studies, ionic liquids 1‐butyl‐3‐methylimidazolium bromine and 1‐(4‐ethenylbenzyl)‐3‐(3,3,4,4,5,5,6,6,7,7,8,8,8‐tridecafluorooctylimidazolium iodide (ETI) were used as additives in MA + ‐contained perovskite precursor solutions. In the latter case, it was shown that the formation of hydrogen bonds between ILs and MA restrains the MA + cation movement from bulk to the surface, resulting in enhanced thermal stability (Figure d).…”
Section: Progress On Additive Engineering During Perovskite Formationmentioning
confidence: 99%
“…HMII can reduce the trap density and prevent the notorious ion migration from the perovskite lattice by anchoring the migrating ions with nonvolatile [HMI] + cations through ionic interactions. [ 54 ] On the other hand, the presence of defects (especially grain boundaries) may provide a favorable pathway for the migration of such ions due to reduced steric hindrance. [ 55 ] In this respect, HMII can also play a subsidiary role in suppressing possible ion diffusion as a result of the formation of high‐quality FAPbI 3 films with large grain size and reduced grain boundaries where the volatile ions can readily escape.…”
Section: Resultsmentioning
confidence: 99%
“…revealed that the 1‐butyl‐3‐methylimidazolium bromide anchors MA cations through hydrogen‐bonding (HB) interactions, thus reducing the grain boundaries of perovskite films. [ 27 ] 1‐Hexyl‐3‐methylimidazolium chloride facilitated the formation of homogeneous nucleation sites and prevented crystallization of MAPbI 3 from over‐speeding. [ 28 ] 1‐Methyl‐3‐allylimidazolium iodide (CC2) with the side‐chain of ‐CH 2 ‐CHCH 2 presented a PCE of 19.2% from a 3D PVSC, and it was found that CC2 coordinated with PbI 2 to form imidazolium‐PbI 3 − salts through HB interactions, resulting in an effective crystal growth control.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Du et al revealed that the 1-butyl-3-methylimidazolium bromide anchors MA cations through hydrogen-bonding (HB) interactions, thus reducing the grain boundaries of perovskite films. [27] 1-Hexyl-3-methylimidazolium chloride facilitated the formation of homogeneous nucleation sites and prevented crystallization of MAPbI 3 from over-speeding. [28] 1-Methyl-3-allylimidazolium iodide (CC2) with the side-chain of -CH 2 -CHCH 2 presented a In optimizing perovskites with ionic liquid (IL), the comparative study on Lewis acid-base (LAB) and hydrogen-bonding (HB) interactions between IL and perovskite is lacking.…”
mentioning
confidence: 99%